2006
DOI: 10.1038/sj.ejcn.1602493
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption and feeding patterns of Czech infants and toddlers living in Prague

Abstract: Objective: To describe feeding patterns during first two years of life and their relation to sociodemographic factors. Design: Longitudinal study. Setting: Prague, Czech Republic. Subjects: Ninety-seven full-term healthy singletons enrolled at maternity ward, of which 90.7% completed the study. Methods: Diet was assessed at 9, 12 and 24 months of age using a structured 3-day dietary record. Additional information was obtained from questionnaires completed at birth and at 6 months. Results: The median duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…Meat products, fish, poultry, dairy products and vitamin A-rich foods are consumed infrequently by young children; however, the consumption levels tend to increase with children's age. Likewise, other studies in Kenya (Mutie et al 2010), South Africa (Faber 2004), China (Dang et al 2005) and South Asia (Kudlova & Rames 2007;Joshi et al 2012;Kabir et al 2012;Patel et al 2012;Senarath et al 2012b) have also reported similar trends. Limited opportunities to access these foods have been reported to be the main limiting factor for their daily consumption (Dang et al 2005).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Meat products, fish, poultry, dairy products and vitamin A-rich foods are consumed infrequently by young children; however, the consumption levels tend to increase with children's age. Likewise, other studies in Kenya (Mutie et al 2010), South Africa (Faber 2004), China (Dang et al 2005) and South Asia (Kudlova & Rames 2007;Joshi et al 2012;Kabir et al 2012;Patel et al 2012;Senarath et al 2012b) have also reported similar trends. Limited opportunities to access these foods have been reported to be the main limiting factor for their daily consumption (Dang et al 2005).…”
Section: Discussionsupporting
confidence: 61%
“…), South Africa (Faber ), China (Dang et al . ) and South Asia (Kudlova & Rames ; Joshi et al . ; Kabir et al .…”
Section: Discussionmentioning
confidence: 99%
“…A significant connection between the early introduction of CF and infants being fed combined milk nutrition has been confirmed by many other studies (Hendricks et al, 2006;Grummer-Strawn et al, 2008;Schiess et al, 2010). Lower age and education of mothers participating in our research, as well as in some other studies, (Kudlova, Rames, 2007;Rebhan et al, 2009;Scott et al, 2009;Tarrant et al, 2010;Brodribb, Miller, 2013;Kronborg et al, 2014) constitute risk factors for the early introduction of CF. Analysis of the research results suggests a significant increase in likelihood in relation to decreasing levels of maternal education.…”
Section: Discussionsupporting
confidence: 81%
“…A Finnish study 12 reported recently that longer duration of breastfeeding was associated with more years of parental education and older age of the mother. In a Czech study, higher maternal education was associated with longer duration of exclusive breastfeeding 25.…”
Section: Discussionmentioning
confidence: 94%